Development of a PVDF sensor for potted seedling clamping force of vegetable transplanting - Ji, Jiangtao; Sun, Jingwei; Jin, Xin; Li, Mingyong; Du, Xinwu (International Journal of Agricultural and Biological Engineering, 2019)
Aiming at the problems of loose bowl, nutritive bowl damage and planting leakage caused by lack of perception and detection of seedling clamping force in vegetable transplanting, a semi-micro-column structure sensor for measuring potted seedling clamping force was developed based on polyvinylidene fluoride (PVDF) piezoelectric film. The diameter of the semi-micro-column is 4 mm. The size of the force probe is 14 mm×30 mm, the encapsulation position of the force probe is 25 mm away from the tip of the seedling claw. The hardware circuit for sensor signal acquisition including pre-amplification module, power frequency notch module, low-pass filter module, processor module and power module was designed. The circuit completes charge-voltage conversion, clamping force signal amplification, power frequency signal elimination, vibration and noise elimination, and ensures the accurate acquisition of clamping force signal. In order to verify the sensor performance, sensor calibration tests and indoor experiments were carried out respectively. The calibration tests showed that the sensitivity of the clamping force sensor was 0.5264 V/N, the linearity was 4.74%, the accuracy was 6.51%, the hysteresis was 3.63%, and the range was 8 N under the impact of different waveforms and frequencies, which fully meet the accuracy requirements of the clamping force detection during transplanting. Indoor experiments showed that the clamping force sensor had good stability and adaptability under different seedling frequencies. The sensor can provide useful reference for the perception and detection of seedling clamping force and the feedback regulation of seedling clamping force.Keywords: seedling clamping force, PVDF piezoelectric film, semi-micro-column structure, hardware circuitDOI: 10.25165/j.ijabe.20191205.5094Citation: Ji J T, Sun J W, Jin X, Li M Y, Du X W. Development of a PVDF sensor for potted seedling clamping force of vegetable transplanting. Int J Agric & Biol Eng, 2019; 12(5): 111–118.